Task switching in English-Chinese bilinguals : a life-span approach - Low, Joel Jia Wei (2013)
Switching between tasks is essential in daily function. The current study investigated the life-span development of cognitive flexibility in Singaporean English-Chinese bilinguals. Task switching involves maintaining and updating information, integrating task sets, suppressing previously active task sets, and disinhibiting previously suppressed task sets. [3rd Award]-[Peer Assessment Review]